PERBEDAAN PENGETAHUAN DAN SIKAP SISWA TENTANG HIV/AIDS SEBELUM DAN SESUDAH PENYULUHAN DI SMA ISLAM PB SOEDIRMAN 2020 - Fathia Athifarini (2020)
In 2019 DKI Jakarta had 6,701 HIV cases and 585 AIDS cases with 18.2% of teenagers. Teenagers are at risk because of a lack of knowledge about HIV / AIDS. Therefore, it is necessary to hold health education about HIV / AIDS. The purpose of this study was conducted to determine differences in students' knowledge and attitudes before and after counseling was conducted using PowerPoint and Google form distributed through the WhatsApp group. The method used in this study is Pre-experimental research design with one group pre-test post-test to class XI students of Islamic High School PB Soedirman, East Jakarta. This research was conducted in June 2020 with a total sample of 109 students. Wilcoxon statistical test results on the knowledge and attitudes of respondents obtained a P-value of 0,000. These results indicate that there are significant differences in knowledge and attitudes before and after health promotion in schools. It is recommended that regular HIV / AIDS counseling be carried out and include subject matter about HIV / AIDS health in schools.